Solid-liquid mass transfer in agitated newtonian and non-newtonian fluids - Lal P.; Kumar S.; Upadhyay S.N.; Upadhya Y.D. (My University, 2025)
Diffusional mass-transfer rates were experimentally measured by following the rate of dissolution of benzoic acid pellets and spheres (diameter 0.513-2.008 cm) suspended in agitated Newtonian (water, ethylene glycol, and 60% aqueous propylene glycol solution) and in non-Newtonian (1.0%, 2.0%, and 3.0% aqueous (carboxymethyl)cellulose (CMC) solutions) fluids in baffled and unbaffled vessels of diameter 14.5-25.0 cm using disk turbine, plane turbine, and propeller agitators. The influences of various operating and physicochemical parameters were investigated. The results are correlated in terms of dimensionless groups. © 1988, American Chemical Society. All rights reserved.